IMPLEMENTASI KEBIJAKAN PEMBERDAYAAN MASYARAKAT MELALUI MUSRENBANGDES TERHADAP PEMBANGUNAN DESA: STUDI KASUS DI DESA SAMPALI, KECAMATAN PERCUT SEI TUAN - Devi Permata Br Bangun; Herlide Purba; Seevaira Chyta Simanullang; Julia Ivanna (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyze the implementation of community empowerment policies through the Village Development Planning Meeting (Musrenbangdes) in the development process of Sampali Village, Percut Sei Tuan Subdistrict. Musrenbangdes is a participatory forum designed to actively involve village communities in planning both physical and non-physical development. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation. The research findings indicate that the implementation of Musrenbangdes in Sampali Village has aligned with the principles of participation, transparency, and accountability. The involvement of various community elements demonstrates democratization in the village development planning process. However, challenges remain regarding the quality of participation due to limited access to information and policy literacy. Therefore, the active role of facilitators in providing political education is crucial to enhancing the effectiveness of empowerment. Overall, the implementation of this policy reflects the spirit of the Village Law, which places the community as the main subject of village development.